The role of the international community in a new model of reforming the political and social architecture of Bosnia and Herzegovina - Juvan, Janez (Varstvoslovje, 2022)
Purpose: For decades, the international community has been trying to contribute to long-term peace and stability in Bosnia and Herzegovina (BiH), but it has been only partially successful. The purpose of the paper is to present a new model for the reform of the political and social architecture, which, along with the new role of the international community, will ensure the peace, stability and security of BiH, and at the same time will be applicable in other areas of the world. Design/Methods/Approach: The article brings insights in the mentioned processes by using combinations of theoretical and empirical methods, of which the most important are in-depth interviews with experts who know the region in detail, as well as the measures already implemented in (post)conflict areas in some other parts of the world. Findings: The article discusses a possible model for the future role of the international community in this country as developed by the Working Group on BiH. The model relies on technical assistance to the country for fundamental reforms provided by highly qualified international experts using a modular reform implementation strategy. It is a modular implementation of the reforms, which increases the efficiency and at the same time checks the suitability of the proposed solutions. Research Limitations/Implications: The situation in BiH is very complex due to the complicated political system, the ethnic map, the political situation, the economic and social situation, therefore, generalizing the findings is difficult. Practical Implications: Reforms must strengthen the rule of law, modernize public administration, harmonize the business environment through fiscal policy and control institutions, open and protect labour competitiveness, establish functioning social, health, and pension systems, and open up space for civil society. Originality /Value: Article is presenting the new model as a regional integration programme for infrastructure, economy, education, inter-institutional cooperation, culture, and sports.
Keywords: Bosna in Hercegovina; Bosnia and Herzegovina; EU accession; international community; mednarodna skupnost; new reforms model; nov model reform; priključitev EU